(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2024)
The rapid advancement in technology has made computer graphics an essential skill for students. This article explores strategies and methods to enhance computer graphics competency among school students. It discusses the importance of integrating computer graphics education into the curriculum, effective teaching practices, and the use of various software tools to improve students’ proficiency. Additionally, the article highlights the benefits of developing computer graphics skills, such as improved creativity, problem-solving abilities, and future career opportunities.